Anomalous scattering factor using proton induced X-ray emission technique. (February 2015) - Latha, P.; Magudapathy, P.; Abdullah, K.K.; Nair, K.G.M.; Babu, B.R.S.; Varier, K.M.
Abstract: Atomic scattering factor is in general a complex number represented by the sum of normal scattering factor ( f 0 ) and anomalous scattering factors [real ( f ′ ) and imaginary ( f ″ ) ]. Anomalous scattering factors in Ag, In, Cd and Sn were determined experimentally from attenuation data measured using PIXE and compared with theoretical values. The data cover the energy region from 10 to 30 keV and atomic number Z from 47 to 50 keV. Our results found to be in close agreement with theoretical values. Abstract : Highlights: Anomalous scattering factors determined from the attenuation data. PIXE technique is used for getting the attenuation data. Our results are in close agreement with the available theoretical values. PIXE technique is a reliable tool for determining anomalous scattering factors.